2012
DOI: 10.1016/j.genhosppsych.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Onset and risk factors for anxiety and depression during the first 2 years after lung transplantation

Abstract: Objective Anxiety disorders are prominent in chronic lung disease; lung transplant recipients may therefore also be at high risk for these disorders. We sought to provide the first prospective data on rates and risk factors for anxiety disorders as well as depressive disorders during the first two years after transplantation. Method 178 lung recipients, and a comparison group (126 heart recipients), received psychosocial and Structured Clinical Interview for DSM-IV assessments at 2-, 7-, 12-, 18-, and 24-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 67 publications
2
84
2
4
Order By: Relevance
“…Emerging work suggests that constructs relevant in older populations such as frailty, depression, and cognitive impairment may be important. (10, 11, 19, 20)…”
Section: Discussionmentioning
confidence: 99%
“…Emerging work suggests that constructs relevant in older populations such as frailty, depression, and cognitive impairment may be important. (10, 11, 19, 20)…”
Section: Discussionmentioning
confidence: 99%
“…However, it would remain within the norm after LT, even as patients cope with complicated posttransplant medical regimens and treatment side effects, because of a revision in patients' HRQoL standards: patients would be more conscious of the fact that their lives had been prolonged thanks to a gift that implied another person's death [15,30]. This further explains why MCS pattern did not change over time in either survivors or non-survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is little evidence of the precise involvement of mental health in LT outcomes. Recently, Dew et al [15] focused on anxiety disorders after LT, and concluded that lung and cardiothoracic recipients appear more susceptible to panic disorders and panic-related depression. However, there is little consensus with respect to the psychometric instruments used in such investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic literature review was conducted based (Kierans, 2005(Kierans, , 2011Sharp, 1995;Shimazono, 2008). Sin embargo, se ha identificado una tendencia a enfocarse solo en la dimensión biológica del trasplante, a partir del legado de un discurso médico positivista que manifiesta que el éxito del trasplante reside en la correcta asimilación del órgano o tejido (Burra et al, 2007;De Bona et al, 2000; Martín-Rodríguez, Fernández-Jiménez, Pérez-San-Gregorio, Pérez-Bernal y Gómez-Bravo, 2013; Muehrer y Becker, 2005) y en las motivaciones del donante -debido a la necesidad de lograr una mayor tasa de donaciones en el mundo, significativamente baja en algunos países-(Global Observatory on Donation & Transplantation [GODT], 2012; Mahillo, Carmona, Álvarez, Noel y Matesanz, 2013;Mizraji et al, 2007; World Health Organization [WHO], 2009).A pesar de ello, han adquirido relevancia factores como el aumento en la supervivencia postrasplante y la redefinición de los criterios para valorar el éxito de la intervención (Anand-Kumar, Kung, Painter y Broadbent, 2014;Dew et al, 2012; Hoodin y Weber, 2003; Pérez, Martín, Gallego SIGNIFICADOS DEL TRASPLANTE 21 y Santamaría, 2000; Taşkintuna y Ozcurumez, 2011). Por consiguiente, el interés en la dimensión psicológica y en la calidad de vida de los receptores, durante el proceso de trasplante, ha aumentado notoriamente en el campo investigativo (CrowleyMatoka, 2005;Kierans, 2005;Sanner, 2001).…”
unclassified